THE EFFECT OF SLING-BASED MANUAL THERAPY AND STABILIZATION EXERCISE FOR IMPROVING CERVICAL ALIGNMENT AND MOBILITY IN INDIVIDUAL WITH FORWARD HEAD POSTURE - Kamayoga, I Dewa Alit; Adyasputri, A A I Ayesa Febrinia; Adhitya, I Putu Gde Surya; Putra, I Putu Yudi Pramana; Widnyana, M; Utama, Anak Agung Gede Eka Septian (Sport and Fitness Journal; Vol 10 No 3 (2022): Volume 10, No.3, September 2022, 2022)
Individual that greater use of information and communication technologies such as computer, smartphone, or other media has the tendency failure of body postures. Laptop usage has been associated with adolescent neck pain, with daily use of computers exceeding 2-3 hours as a threshold to forward head posture. Forward head posture can affect the result of reducing cervical alignment and mobility of the neck. There are exercises that intention to improving the cervical alignment and mobility, particularly sling-based manual therapy and stabilization exercise. A sling device provide the research subject with optimal loading of each target segment, in actual neutral position, and an environment for exercise in a closed kinetic chain. Spinal mobilization techniques used in manual spinal treatment activate the descending pathway from the peritubular gray region (PAG) of the midbrain. Moreover, stabilization exercise affect postural control through concurrent contractions of the agonist and antagonist muscles to improving cervical alignment and mobility. Key Words: Sling; Manual Therapy; Stabilization Exercise; Cervical Alignment; Cervical Mobility; Forward Head Posture